Understanding the Dynamics of Islamic Media: A Comparative Analysis of Lensamu and Aisyiyahpusat Instagram Accounts’ Digital Communication Strategies - Hakim, Lukman; Sumarlan, Iman (Universitas Ahmad Dahlan, 2025)
The purpose of this research is to examine the dynamics of Islamic media on Instagram via a comparative analysis of two da'wah accounts, Lensamu and Aisyiyah Pusat. This study uses a qualitative methodology and content analysis to investigate differences in digital communication methods, message framing, and audience interaction patterns across both accounts. Primary data were taken from Instagram uploads over a specific time period, while secondary data were gathered from literature on digital communication and Islamic media. The study's findings suggest that Lensamu uses an engaging and inspiring visual approach to catch the attention of the younger population with light and easy-to-understand material. Aisyiyahpusat, on the other hand, employs a more formal and analytical communication style, focussing on in-depth material presentation and critical conversations that foster excellent interactions. These findings emphasize the significance of tailoring digital da'wah techniques to audience characteristics, as well as contributing to the creation of more adaptable Islamic communication approaches in the age of social media.